Screening for carbapenemase-producing Enterobacteriaceae in previous carriers readmitted to hospital: evaluation of a change in screening policy. Issue 2 (October 2019) - Tucker, A.; George, R.; Welfare, W.; Cleary, P.; Cawthorne, J.; Dodgson, A.
Summary: Carbapenemase-producing Enterobacteriaceae (CPE) are a growing problem in UK hospitals. Preventing transmission requires early detection. This study evaluates a new screening policy for patients with a history of blaKPC-associated CPE (KPC-CPE) in a higher incidence hospital. Previous policy assumed 'once positive always positive'. New policy uses rapid screening and risk assessment. Results show that most (76.5%) patients with a history of KPC-CPE do not have detectable KPC-CPE on readmission or during their subsequent hospital stay but that repeat screening after an initial negative result is required. The new policy takes a risk-based approach while prioritizing isolation facilities in a higher incidence trust.